2021
DOI: 10.3389/fbioe.2021.673314
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ethanol Extracts From Alnus sibirica Fisch. ex Turcz in Hair Growth Promotion

Abstract: Alnus sibirica Fisch. ex Turcz (ASFT), belonging to the family of Betulaceae, grows naturally in Asia, Europe, and America. The aims of this study are determining the efficacy of various biomarkers related to hair loss, evaluated by extracting the branch with 60% alcohol, and purely separating diarylheptanoid oregonin, an indicator and active substance, from 60% alcohol extract of the tree. To determine the preventive effects on hair loss, we investigated the anti-oxidative and anti-apoptotic effects on hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In many similar studies, an optimal extraction method was developed to obtain large quantities of effective substances from the same amount of natural raw materials while considering cost, space, facilities, and infrastructure (Liu et al, 2017;Hu et al, 2018;Lu et al, 2019;Kumar et al, 2020;Wang et al, 2020;Xu et al, 2020c;Yang et al, 2020;Ha et al, 2021;Huang et al, 2021;Zheng et al, 2021). Accordingly, the most commonly used extraction methods in academia and industry include hot water extraction, ethanol extraction, ultrasonic extraction, pressurized extraction, and supercritical extraction (Si et al, 2011;Chen et al, 2016;Hu et al, 2017;Xie et al, 2018Xie et al, , 2019Yang et al, 2019;Xu et al, 2020aWang et al, 2021a;Liu et al, 2021aLiu et al, , 2021bLiu et al, , 2021c.…”
Section: Antiapoptotic Effects On U937 Cellsmentioning
confidence: 99%
“…In many similar studies, an optimal extraction method was developed to obtain large quantities of effective substances from the same amount of natural raw materials while considering cost, space, facilities, and infrastructure (Liu et al, 2017;Hu et al, 2018;Lu et al, 2019;Kumar et al, 2020;Wang et al, 2020;Xu et al, 2020c;Yang et al, 2020;Ha et al, 2021;Huang et al, 2021;Zheng et al, 2021). Accordingly, the most commonly used extraction methods in academia and industry include hot water extraction, ethanol extraction, ultrasonic extraction, pressurized extraction, and supercritical extraction (Si et al, 2011;Chen et al, 2016;Hu et al, 2017;Xie et al, 2018Xie et al, , 2019Yang et al, 2019;Xu et al, 2020aWang et al, 2021a;Liu et al, 2021aLiu et al, , 2021bLiu et al, , 2021c.…”
Section: Antiapoptotic Effects On U937 Cellsmentioning
confidence: 99%
“…Numerous efforts to find anti-alopecia plant extracts have previously been conducted [51][52][53]. Here, we found that Cs-EE can alleviate 5α reductase activity, which inhibited the protein expression of AR.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, the usages of these m life-care products, as opposed to medicinal drugs, specifically need to target su tions. Second, results may depend on the extraction methods of included raw possible unpublished reports had different characteristics within certain facilit ample, given that the extracts were in a complex, multifaceted condition for In previous reports, we determined cell viabilities in HFDPCs and other cells after challenges of oxidative stress or immunotoxic agents such as hydrogen peroxide [38] or lipopolysaccharides [39], respectively. Moreover, these effects were defined as multifunctional regulation through anti-oxidative, anti-inflammatory and/or anti-microbial pathways [39,40].…”
Section: Resultsmentioning
confidence: 99%